Does teachers’ self-reported growth mindset ensure growth mindset-oriented feedback practices in the classroom? - Zhang, Kai; He, Wu-jing (Frontiers in Education, 2024)
This study examined the congruence/incongruence between teachers’ self-reported mindset beliefs and their actual teaching practices within the framework of implicit theories of intelligence. A total of 226 middle school teachers (65.90% female, average age = 31.70 years, SD = 5.03; average education year = 16.23, SD = 1.49; average teaching experience = 6.52 years, SD = 4.17) from Shanghai City, mainland China, completed the growth mindset inventory (GMI) for measuring self-reported growth mindset beliefs and underwent classroom observations, which recorded the frequency of their growth mindset-oriented feedback practices while teaching. Subsequently, the 20 teachers with the most extreme GMI scores (i.e., the 10 teachers with the highest scores and the 10 teachers with the lowest scores from this initial pool) were invited to take part in semi-structured interviews to understand the reasons behind the possible congruence/incongruence. Interesting results were found. First, the results of the spearman correlation and multiple regression analyses suggested incongruence between teachers’ self-reported mindset beliefs and their actual feedback practices in real classroom settings for those with growth and neutral mindsets but congruence for those with fixed mindsets. Second, the results of the semi-structured interviews further illustrated that whether teachers demonstrated congruence/incongruence in their growth mindset beliefs and actual growth mindset-oriented feedback practices in the classroom was influenced by contextual factors such as institutional policies, cultural orientations, community expectations, and the general educational competition environment. These findings contribute to a deeper understanding of the factors influencing the alignment between mindset beliefs and teaching practices, which highlight the need for addressing these discrepancies in teacher development programs.